DAMPAK BENCANA KEKERINGAN TERHADAP PELUANG KESEJAHTERAAN PENDUDUK - Y. B. Widodo (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2007)
Natural disasters that happened lately in many parts of the world, especially drought and big flood in Indonesia, are accumulative effects of climate change due to global warming that need to be addressed seriously. However, the most important issue in Indonesia nowadays is natural disaster that happens in conjuction with mass-impoverishment effected by unleashed human greed. If this excessive lifestyle cannot be restrained, the country of Indonesia will face an incurable ecological destruction. This article tries to address natural disasters from socio- economic and socio-demographical aspects.